Complex Immunometabolic Profiling Reveals the Activation of Cellular Immunity and Biliary Lesions in Patients with Severe COVID-19 - Klocperk, Adam (J Clin Med, 2020)
This study aimed to assess the key laboratory features displayed by coronavirus disease 2019 (COVID-19) inpatients that are associated with mild, moderate, severe, and fatal courses of the disease, and through a longitudinal follow-up, to understand the dynamics of the COVID-19 pathophysiology. All severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-positive patients admitted to the University Hospital in Motol between March and June 2020 were included in this study. A severe course of COVID-19 was associated with an elevation of proinflammatory markers; an efflux of immature granulocytes into peripheral blood; the activation of CD8 T cells, which infiltrated the lungs; transient liver disease. In particular, the elevation of serum gamma-glutamyl transferase (GGT) and histological signs of cholestasis were highly specific for patients with a severe form of the disease. In contrast, patients with a fatal course of COVID-19 failed to upregulate markers of inflammation, showed discoordination of the immune response, and progressed toward acute kidney failure. COVID-19 is a disease with a multi-organ affinity that is characterized by the activation of innate and cellular adaptive immunity. Biliary lesions with an elevation of GGT and the organ infiltration of interleukin 6 (IL-6)-producing cells are the defining characteristics for patients with the fulminant disease.